Pengaruh Model Project-Based Learning terhadap Kemampuan Pemahaman dan Disposisi Matematis Siswa pada Materi Pengelolaan Data - Rahmawati, Devi; Maulana, Maulana; Djuanda, Dadan (Jurnal Pena Ilmiah, 2019)
Mathematics is anvimportant science for life. Also besides, mathematics is the basis for other sciences, so it is important to master mathematical understanding and disposition skills. Through the project-based learning model, the teacher optimizes learning to improve mathematical understanding and disposition. This study aims to determine the increase in mathematical understanding and disposition through project-based learning models and conventional models and to find out the positive relationship between mathematical understanding andidisposition ability. This study used a quasi-experimental method with the design of the nonequivalent control group design. The population in this study were all fourth-grade students in Cicalengka District, with a sample of fourth-grade students at SDN Leuwiliang (experiment), and SDN Dampit 01 (control). Conclusions from this study are, 1) Project-based learning models and conventional models can improve mathematical understanding and disposition skills, 2) Project-based learning models are better at improving mathematical understanding and disposition than conventional models, 3) There is a positive relationship between the ability of understanding and mathematical disposition.Project-based Learning Model, Mathematical Understanding Ability, Mathematical Disposition.